Asuhan Keperawatan pada Ny.P Dengan Sc Indikasi IUFD Akibat Solusio Plasenta di Ruang Nusa Indah RSUD Dr. Soeselo Kabupaten Tegal - Saskiana Dewi; Tati Karyawati; Siti Fatimah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
When problems such as antepartum hemorrhage, fetal distress, atypical fetal presentation, and gestational hypertension occur, a cesarean section can save the lives of both mother and baby. A cesarean section (CS) is a surgical technique in which the uterus and abdominal wall are opened to deliver the fetus. In many countries, cesarean sections are the most common surgical procedure, and over the past 30 years, their use has gradually increased. Intrauterine fetal death is the death of a fetus weighing 500 grams or more in the womb at 20 weeks of gestation or later. The partial or complete separation of a normally implanted placenta after 22 weeks before birth is known as placental abruption. he purpose of this paper is to provide nursing care to Mrs. P with a Caesarean section indicating intra uterine fetal death (IUFD) due to placental abruption in the Nusa Indah room of dr. Soeselo Regional General Hospital, Tegal Regency, according to nursing standards. The method used is descriptive with a case study approach. The data collection techniques in this scientific paper are in the form of interviews, observations, documentation studies and literature studies. From the case review, the main complaint was pain in the operated area, pain increased when moving, pain like being squeezed with a pain scale of 5, pain that comes and goes. The patient appeared to be grimacing in pain and restless, the patient always held the area that had been operated on, the results of the vital signs examination obtained: BP: 139/100 mmHg, pulse: 103 x / minute, S: 36.5oC, RR: 20 x / minute, there was a bandage on the lower abdomen along 15 cm with a horizontal line, the patient did not know and was confused about the birth control used after the CS. The nursing problems identified were acute pain, risk of infection, and knowledge deficit. Interventions were developed based on the theory in the SDKI, SLKI, and SIKI, as well as the client's condition, and were implementable